Rational financial management: Evidence from seasoned equity offerings - BARCLAY, Michael (Institutional Knowledge at Singapore Management University, 2012)
Current theories of capital structure have difficulty explaining the aspects of financing behavior we document. In contrast to the tradeoff theory, seasoned equity offers frequently move firms away from their target leverage ratios. At odds with the pecking-order theory, SEO firms typically are financially healthy companies with low leverage, unused debt capacity and substantial cash balances. Inconsistent with the market-timing theory, SEOs appear to be driven by capital requirements associated with large investment projects rather than by market-timing considerations. Moreover, firms issue debt following SEOs, not only to finance investment, but to increase leverage toward its target level. Each of these theories assumes some degree of myopia among financial managers. We propose that CFOs manage their capital structures rationally rather than myopically. They consider the firm’s current and target leverage, investment opportunities and long-term capital requirements, as well as the costs and benefits of alternative sequences of financing transactions. This framework, which we term rational financial management, better explains the financing and leverage behavior of SEO firms.